Peran Guru dalam Menstimulus Respon Anak melalui Teori Belajar Behavioristik: The Role of the Teacher in Stimulating Children's Responses through Behavioristic Learning Theory - Suswandari, Meidawati (Absorbent Mind, 2021)
The aims of this study are 1) to describe the method used by teachers in stimulating student responses through behavioristic theory, and 2) to describe the benefits of teachers stimulating student responses through behavioristic learning theory. This research method using literature study. The object of this research is behavioristic learning theory. The subjects of this research are teachers and children. Meanwhile, the data collection tool used in this research was through a search for scientific journals that I took from several electronic media such as digital libraries, the internet, and Google Scholar. The data analysis technique used in this research is annotated bibliography analysis. The results show that 1) the method used by the teacher in stimulating student responses is through behavioristic theory, namely the teacher must understand the differences in children’s with their respective characteristics, the teacher ensures that children’s are ready to learn, the teacher provides stimulus in the form of objects, non-objects, and gestures and the teacher provides good modeling/imitation to children’s , 2) the benefits of the teacher stimulating student responses through behavioristic learning theory, namely raising student interest in learning through the use of creative and fun learning stimuli so as to get positive responses from children’s . Adapun tujuan penelitian ini yakni 1) mendeskripsikan cara yang digunakan guru dalam mentimulus respon anak melalui teori behavioristik, dan 2) mendeskripsikan manfaat guru menstimulus respon anak melalui teori belajar behavioristik. Metode penelitian ini dengan menggunakan studi pustaka. Obyek penelitian ini adalah teori belajar behavioristik. Subyek penelitian ini yakni guru dengan anak. Sedangkan alat pengumpulan data yang digunakan penelitian ini melalui penelusuran jurnal ilmiah yang saya ambil dari beberapa media elektronik sebagimana dalam digital library, internet, dan Google Cendekia. Adapun teknik analisis data yang digunakan pada penelitian ini yakni analisis anotasi bibliografi (annotated bibliography). Hasil penelitian menunjukan bahwa 1) cara yang digunakan guru dalam menstimulus respon anak melalui teori behavioristik yaitu guru harus memahami perbedaan anak dengan karakteristiknya masing-masing, guru memastikan bahwa anak telah siap untuk belajar, guru memberikan stimulus berupa benda, non benda, dan isyarat, serta guru memberikan pemodelan/peniruan yang baik pada anak, 2) manfaat guru menstimulus respon anak melalui teori belajar behavioristik yaitu memunculkan minat belajar anak melalui penggunaan stimulus pembelajaran kreatif dan menyenangkan sehingga mendapatkan respon positif dari anak.